TRANSMISSION OF NARROW SOUND BEAMS IN NONLINEAR ENVIRONMENT - Manukyan, S.M.; Butavyan, A.A.; Manukyan, H.M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In the paper we consider the problem of the transmission of limited sound beams. The transmission of such beams is described by a nonlinear partial differential equation. In the paper we solve this equation by the latticecharacteristics method. Some numerical results are obtained for a special case.